Strategic Dividend Policy Adaptation and Stock Market Reactions in State-Owned Enterprises Across Crises - Georgina Maria Tinungki; Powell Gian Hartono; Nurhafifah Amalina; Dewie Tri Wijayati Wardoyo; Reniati Karnasi; Gatri Lunarindiah; Marieta Ariani; Lidia Wahyuni (Ital Publication, 2026)
This study investigates the strategic adaptation of dividend policy in Indonesian state-owned enterprises across the pre-crisis, crisis, and recovery phases. Adaptation is operationally defined as firm-level, measurable changes in cash dividend indicators during the crisis and post-crisis phases relative to the pre-crisis average. Empirically, dividend behavior is estimated using a dynamic panel framework with system GMM, and an event-study approach evaluates abnormal returns and cumulative abnormal returns around dividend announcement dates in each phase. The results indicate that SOEs increased dividends during the crisis relative to pre- and post-crisis periods, and that the market exhibited stronger positive reactions in the crisis and recovery phases than in the pre-crisis phase. These patterns suggest adaptive choices consistent with managing uncertainty and reinforcing policy credibility within Indonesia’s state-ownership setting. The findings highlight the strategic role of dividend signals in shaping investor perceptions during economic shocks, while theoretically challenging the core cash-conservation premise of the pecking order and reinforcing the relevance of signaling theory for state-controlled firms with complex fiscal and political mandates.